2007
DOI: 10.1529/biophysj.106.092361
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Spine Viscoelasticity and Soft-Glassy Nature: Balancing Dynamic Remodeling with Structural Stability

Abstract: Neuronal dendritic spines are a key component of brain circuitry, implicated in many mechanisms for plasticity and long-term stability of synaptic communication. They can undergo rapid actin-based activity-dependent shape fluctuations, an intriguing biophysical property that is believed to alter synaptic transmission. Yet, because of their small size (approximately 1 microm or less) and metastable behavior, spines are inaccessible to most physical measurement techniques. Here we employ atomic force microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 72 publications
2
27
0
Order By: Relevance
“…Our data are consistent with recent atomic force microscope measurements that record five-fold greater viscosity in dendritic spines than in cell body (Smith et al 2007). (ii) Macromolecular crowding: Sieving and excluded volume effects associated with macromolecular crowding cannot presently be studied well by Smoldyn.…”
Section: In Neuronssupporting
confidence: 92%
See 1 more Smart Citation
“…Our data are consistent with recent atomic force microscope measurements that record five-fold greater viscosity in dendritic spines than in cell body (Smith et al 2007). (ii) Macromolecular crowding: Sieving and excluded volume effects associated with macromolecular crowding cannot presently be studied well by Smoldyn.…”
Section: In Neuronssupporting
confidence: 92%
“…The simulated "best-fit" (see Section 4) estimate was ca. 20 cp; roughly two-fold lower than viscosity reported for dendritic spines (Smith et al 2007). The FRAP curve expected if the viscosity was that measured from FRAP of animal cells (3.2 cp (Swaminathan et al 1997)) is also shown for comparison.…”
Section: Frap and Rfp Based Measurement Of Cytoplasmic Viscositymentioning
confidence: 71%
“…Although the main mechanical indicator is taken to be elasticity, rheological parameters have also been extracted from living cells using various approaches [129][130][131]. Indentation approaches have been used in conjunction with scanning to produce force maps [41][42][43][44]132] or in single spots on living cells to measure time dependence [125,127].…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient of diffusion of CaMKII was recently estimated to be 2 × 10 −14 m 2 s −1 in the spines of neurons by fluorescence recovery after photobleaching [102]. The molecular weight of aKP enzymes lies in the range of ~50–100 kDa (i.e., an order of magnitude below that of CaMKII [~630 kDa]).…”
Section: Methodsmentioning
confidence: 99%